HOME REMEDIES FOR CURING CONSTIPATION IN PRESCHOOL CHILDREN’S - AN OVERVIEW - Aradhye Rahul Audumber; Shinde Dheeraj S. (International Journal of Applied Ayurved Research, 2017)
Constipation is a very common problem in preschool children. A child is considered constipated when he or she has fewer than three bowel movements in a week; has trouble having a bowel movement; or when the stool (poop) is hard, dry, and unusually large. Preschool children are most affected group with the problems of Constipation. There are variety of causes & treatment for Constipation. There are many medicines available in markets which have their own side effects. There are some home Remedies which cure the Constipation without any side effect. This review article describes all angles related to Constipation-preschool child and its solution via home Remedies.